Facile synthesis and electrical characteristics of n-SnO2/p-NiO nanowire heterojunctions - Thi Thanh Le, Dang; Manh Hung, Chu (Communications in Physics, 2019)
In the current work, we report a facile synthesis of n-SnO2/p-NiO nanowire heterojunctions by a drop-coating approach. The pure SnO2 and NiO nanowires (NWs) were grown by chemical vapor deposition (CVD) and hydrothermal methods, respectively. Morphology, composition and crystal structures of the NWs and heterojunctions were investigated by means of field emission scanning electron microscopy (FESEM), energy dispersive spectroscopy (EDS) and X-ray diffraction (XRD), respectively. The data showed that SnO2 NWs were grown with their average diameter of 200 nm and length of about 10 mm. The NiO NWs were also synthesized with a shorter average length and smaller average diameter compared to those of the SnO2 NWs. The EDS results indicated no impurity present in both SnO2 and NiO NWs. The XRD patterns pointed out the tetragonal rutile and cubic structures of SnO2 and NiO, respectively. Interestingly, electrical properties of the NWs and heterojunctions were studied through the Keithley 2602A sourcemeter-based I-V characterizations. The results confirm the nature of the metal semiconducting oxides. The formation of the n-SnO2/p-NiO heterojunctions was certified through the rectifying behavior of the I-V curves with the rectification ratio of about 5 at ± 3V and 350 oC. The potential energy barrier between the NWs was also estimated to be about 1.16 eV. The band energy structure was also proposed to get insight into characteristics of the n-SnO2/p-NiO heterojunction.